Pembentukan Katekis Zaman Moderen: Memahami Makna Biblis - Teologis Martabat Manusia Dalam Rangka Evangelisasi Baru - Emmeria Tarihoran (Jurnal Pelayanan Pastoral, 2024)
This article discusses the concept of human dignity from a theological and biblical perspective, emphasizing its importance in the mission of the Church. Human dignity is the foundation of inherent rights and is not dependent on social status or cultural background. In the Book of Genesis, humans are created in the image of God (imago Dei), highlighting humanity's unique value and position within creation. This understanding serves as the basis for recognizing human rights at the international level, as articulated in the Universal Declaration of Human Rights by the United Nations. The mission of the Church, as mandated in the Gospel, invites every member, not just the clergy, to engage in evangelization. The Church is expected to convey the Gospel's message in ways relevant to the cultural and social contexts of the communities it serves. This approach allows the Church's message to be more readily accepted and resonate with its audience's hearts. This article emphasizes that human dignity cannot be violated and must be respected in all social and pastoral actions. Acknowledging the dignity of each individual is crucial for promoting societal progress and fostering justice and peace. An awareness of the inherent dignity of humanity is expected to inspire individuals and communities to collaborate toward a more just and compassionate world where every person is valued and respected. Thus, understanding human dignity is vital to building a more harmonious society.